I Congreso De Escuelas De Edificación Y Arquitectura Técnica De España 2021
DOI: 10.4995/edificate2021.2021.13588
|View full text |Cite
|
Sign up to set email alerts
|

Observatorio 2020 de la producción científica de la Arquitectura Técnica en España. Análisis de la evolución de la Investigación en Arquitectura Técnica en la Universidad española

Abstract: Desde hace 6 años se elabora el Observatorio de la Producción Científica de la Arquitectura Técnica (AT), que analiza a docentes e investigadores Arquitectos Técnicos de las universidades españolas. En estos años ha habido una evolución del tipo de docente, así como de los investigadores y su producción científica en la AT. El Observatorio 2020 es la última actualización, recogiendo la  la situación de actual cada universidad, así como la evolución cronológica de las características curriculares de su profesor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Among the limitations of this study, it is worth mentioning that there are no national or international scientific articles that address the scientific production of architecture schools. Only one international study was found in Spain, but it is in the format of a lengthy technical report (Durán 2021). Other similar studies were also found but focused on teaching architects and specific sub-disciplines of architecture (Durán Álvarez 2016;Amado Lorenzo 2020, 2021;Rodríguez et al 2020).…”
Section: Limitationsmentioning
confidence: 96%
“…Among the limitations of this study, it is worth mentioning that there are no national or international scientific articles that address the scientific production of architecture schools. Only one international study was found in Spain, but it is in the format of a lengthy technical report (Durán 2021). Other similar studies were also found but focused on teaching architects and specific sub-disciplines of architecture (Durán Álvarez 2016;Amado Lorenzo 2020, 2021;Rodríguez et al 2020).…”
Section: Limitationsmentioning
confidence: 96%